Direct Development of Golf Ball Sponges, Genus Craniella (Demospongiae, Tetractinellida) From the Northeast Atlantic Ocean - Cárdenas, Paco; Chenesseau, Sandrine; Drewery, Jim; Ereskovsky, Alexander (Molecular reproduction and development, 2025)
ABSTRACT Among the eight types of development in sponges, the least common and least studied is direct, non‐larval development during viviparity. To supplement our knowledge of this rare type of demosponge development, we present here a description of the embryonic development of four species of the genus Craniella (Demospongiae, order Tetractinellida) from the deep‐sea in the Northeast Atlantic. Craniella development is asynchronous within one sponge. Mature oocytes are polylecithal and isolecithal. Embryonic development occurs in a dense double‐layer follicle: layers of flattened cells and a thick layer of collagen. The cleavage is total, unequal, and asynchronous. It is characterized by collagen layers penetrating inside the embryo and surrounding blastomeres. As a result of cleavage, an oval‐shaped apolar stereoblastula is formed. At the stereoblastula stage, embryonic sclerocytes secrete the first megascleres, long thin oxeas, radially positioned. Later, the embryo is divided into the peripheral, intermediate, and central zones. In the intermediate zone, choanocyte chambers, lacunes, and canals of the aquiferous system are formed. The fully formed juveniles have a subspherical to flattened shape with cone‐shaped outgrowths on the surface. Unlike the adults, juveniles lack cortical microxeas and have characteristic anamonaenes spicules. The juveniles exit the mother's body through the exhalant canals of the aquiferous system. Trial Registration: Not applicable